Penerapan Model Mind Mapping untuk Meningkatkan Kreativitas Peserta Didik pada Pembelajaran MI Asy-Syafiiyah Kendari - Abdul Rahman; Dalman; Meli Julianti (Yayasan Ishlahul Muslimin Konawe Selatan, 2026)
This research aims to determine the application of the mind mapping model to increase creativity in class IV of MI Asyafiiyah Kendari. This research is Classroom Action Research. The subjects in this research are class IV students of MI Asyafiiyah Kendari in the 2025 academic year with the number 31 students. This research was carried out in 2 cycles where each cycle consisted of planning, action implementation, observation, evaluation and reflection. Each cycle consisted of two meetings. The time for each meeting was 2×35 minutes and every second meeting Evaluation is carried out to determine the increase in student creativity. The results of this research show that students' creativity has increased based on the results of the tests given. Students' learning creativity in thematic learning before taking action obtained an average score of 45.64 with a learning completeness percentage value of 12% or 4 students who obtained a score >70 , and after taking action in cycle I, the results obtained an average score of 66.47 with a completion percentage of 30%, while students who obtained a score >70 increased to 10 students. Then in cycle II, students' learning creativity increased significantly, with an average score of 80.13 and a completion percentage reaching 80%. There were 28 students who got a score >70. Based on this description, it can be said that learning by applying the Mind Mapping model can increase the creativity of learning sides in class IV thematic learning at MI Asyafiiyah Kendari.